El método de Kolb y la lectoescritura en los estudiantes de séptimo grado de la escuela “Luis Alfredo Samaniego Arteaga” Catamayo, 2023 - Herrera Tinizaray, Fanny Esperanza (2023)
The general objective of this research was to determine the effectiveness of Kolb's method rough a didáctica propasar for the development of reading and writing in seventh grade students of the "Luis Alfredo Samaniego Arteaga" basic education school. The Ecuadorian educational system uses the Kolb method in the teaching-learning process, which establishes four phases (experience, reflection, conceptualization, application), allowing the teacher to establish a work plan with playful, creative and dynamic activities aimed at providing students with significant knowledge. The methodological approach used in this study is quantitative-qualitative and its design is non-experimental, in which 38 students and 2 teachers of seventh grade participated. The research methods applied were scientific, analytical, descriptive, descriptive, statistical, as well as techniques such as the interview applied to the teachers and the instruments used were a questionnaire addressed to the students. The results obtained show that the most frequent errors in reading and writing presented by seventh grade students are: rapid reading, not understanding and comprehending a text, not respecting punctuation marks, spelling errors in the use of h, j, g, acute, grave and esdrújulas words. Therefore, it is concluded that the application of the didactic guide based on Kolb's method through experimentation, reflection, conceptualization and application in the teaching process helps to correct the errors in both reading and writing presented by the seventh grade students. Key words: Kolb's method, literacy, teaching-learning, recreational activities